Purification and biochemical characterization of a t/tn specific lectin from lepechinia bullata seeds (LAMIACEAE) (2017)
ABSTRACT Objective: This study focused on purifying and characterizing a lectin from Lepechinia bullata (L. bullata) seeds, and determining its specificity towards tumour-associated carbohydrate-antigens. Methods: Pigments were removed by washing the seeds with NH4OH 0.1 M pH 9.4 and treating the crude extracts with Pectinex®. The purification procedure consisted of anion exchange chromatography on diethylaminoethyl (DEAE)-Sephadex followed by affinity chromatography. For the characterization, the phase was used polyacrylamide gel electrophoresis-sodium dodecyl sulphate (SDS-PAGE), isoelectric focusing, hemagglutination assays, enzyme-linked lectinosorbent assay (ELLA) and thermal shift assay (TSA). Results: 6.2 mg of lectin were obtained from 100 g of seeds. It was able to agglutinate enzymatically treated erythrocytes with a minimal required lectin concentration of 7 μg. ml-1. Strong binding to asialo bovine submaxillary mucine (aBSM) was determined, corroborating Tn recognition. The isoelectric focusing showed a unique band at pH 8.5. Lectin pure shown bands at 28, 48 and 93 kDa by SDS-PAGE, with an incomplete dissociation of the last species despite trying several reduction conditions. By preparative electrophoresis under different conditions, three species were observed too, in all fractions one band at 28 kDa on Tricine-PAGE in reducing and no reducing conditions were found. Amino acid composition, carbohydrate content, thermal stability and Ca2+and Mn2+requirements were determined. N-acetylgalactosamine (GalNAc) and desialylated mucins inhibited the agglutinant activity on human cells. Fetuin inhibited hemagglutination of rabbit erythrocytes. Conclusion: A new lectin was isolated and characterized from L. bullata seeds, it recognizes T/Tn antigen and shows some similarities with other Lamiaceae lectins.